Terrorism: Motivation and Theory - Wayne Korbl (Journal of Public and Professional Sociology)
This paper attempts to determine motivations behind terrorism from the perspectives of Rational Choice Theory and Social Solidarity Theory. Understanding motivation for terrorist acts cannot be determined uni-dimensionally and different levels of terrorist organizations are best understood using different theories – with individual suicide bombers’ motivations best explained by Social Solidarity Theory and sponsoring organizations’ motives best explained by Rational Choice Theory.